DOCHODY BUDŻETOWE A INWESTYCJE KOMUNALNE W GMINACH WIELKOPOLSKICH - Węckowski, Ryszard (Wydział Prawa i Administracji UAM, 2001)
An attempt has been undertaken in the article to evaluate the communes’ income and to establish relation that exist between chosen elements of communal budgets and the level of communal investments. Against the background of information on the level and structure of the income of local self-governmental budgets in the scale of the whole country - the article presents the results of research work made upon the communes that presently do form the new voivodship of Great Poland. This analysis relates to the period 1991 - 1998. Statistical methods proper to structural analysis and to interdependence of such phenomena have been applied in research work. Clear duality is self-evident when examining the communes in question and evaluating them from the point of view of their budgets’ income. On one hand we have to do with quite big group of distinctly poor communes, and on the other - there is relatively small group of communes of an income level that is considerably superior to the average. The second group is mainly consisted with the communes situated in the vicinity of the town of Poznań and some communes in former voivodship of Konin. Richer communes do indeed confine more money for their communal investments (per capita) however they are not leading as far as a share of investments expenses in their budget incomes is concerned. A part of the communes researched runs quickly into debt for to acquire investment means. It is however done by communes of moderate means, semi-municipal and semi-rural in their character. The richest communes must not have recourse to such an indebtedness, and the poorest ones clearly fear the threat of insolvency. The development of particular equipment in the sphere of communal infrastructure proves to have however only a quite general relation with the wealth of a commune. The rhythm of developing chosen kinds of communal equipment in the communes of similar income scale differs often considerably. The text of the article is completed with numerous graphs and diagrams which make evident the differentiation scale of the phenomenons and processes occurring within the analyzed voivodship.
BUGDET INCOME AND COMMUNAL INVESTMENTS IN COMMUNES OF THE GREAT POLAND